Co-existence of Lichen sclerosus et atrophicus and morphoea along Lines of Blaschko - Bikash Ranjan Kar; Kanakalata Dash (Wolters Kluwer Medknow Publications, 2014)
Lichen sclerosus (LS) is an inflammatory dermatitis of unknown etiology that mostly affects the genital region in both the sexes. In active cases the histopathologic changes differentiate between LS and morphoea though in chronic cases it is very difficult to diagnose with certainty. Coexistence of both the conditions in a single patient indicates that these lesions represent a spectrum of similar pathologic process. Coexistence of both the conditions along Blaschko's lines is so far not described in literature. We report an Indian patient with both LS and morphoea occurring along Blaschko's lines.